Evolution of shear strength with varying cement dosages in dredged marine soils - Nordin, Nurul Syakeera; Chan, Chee-Ming (Penerbit Uthm, 2018)
Cement is widely applied in soil treatment to enhance its geotechnical properties. The treatment techniques of dredged marine soils (DMS) are an essential and necessary in assuring the effectiveness for a long-term solution. Particularly the application of it as a backfill material. The reuse of DMS as geomaterial will minimize the impact to environment. The disposal of DMS into the ocean or on land are unsatisfactory in managing its large quantity which indicates a high demand on new ocean and land disposal. DMS are classified as contaminated waste that contain of organic matter and heavy metals. Contaminated DMS can harm aquatic organism, animals and human. It must be disposed safely to ensure the contaminants are not released. This paper presents a cement-treated of Kuala Perlis DMS (3.4 LL) with varying dosage of cement (2.5 – 40 %) at different curing period (1, 168, 336 and 672 hours). It shows the undrained shear strength (su) value of cement-treated DMS throughout the curing process. The results for cement dosage above 20 % shows a good improvement in su value and the strength development were found increased after 168 hours of curing. It was explained that the lowest water-cement (w/c) ratio tend to have a higher su value of the cement-treated DMS.